2002
DOI: 10.1103/physrevc.65.044606
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of finite ground-state spin on fission fragment angular distributions following collisions with spherical or deformed nuclei

Abstract: The influence of the ground-state spin of fusing nuclei on the subsequent fission fragment angular distributions has been investigated through realistic quantum-mechanical calculations. The domain of applicability of an approximate formula is found for spherical nuclei. For deformed nuclei, a generalization of the standard transition state model expression for the fission fragment angular distribution is presented. This predicts dramatic changes in the shape and anisotropy of the distribution, for reactions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Furthermore, Butt et al [345] have demonstrated that fission angular distributions following fusion are very sensitive to the input angular momentum, providing another probe of the reaction mechanism. These predictions could be tested equally well with other isomers such as the K = 15 state in 184 Hf identified in storage-ring measurements [82,83].…”
Section: Isomer Beamsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Butt et al [345] have demonstrated that fission angular distributions following fusion are very sensitive to the input angular momentum, providing another probe of the reaction mechanism. These predictions could be tested equally well with other isomers such as the K = 15 state in 184 Hf identified in storage-ring measurements [82,83].…”
Section: Isomer Beamsmentioning
confidence: 99%
“…Significant cross-section differences will arise using a projectile (or target) of something like the 178 Hf isomer, whose large angular momentum of = π + K 16 would dramatically skew the input l-distributions compared to normal beams. Furthermore, Butt et al [343] have demonstrated that fission angular distributions following fusion are very sensitive to the input angular momentum, providing another probe of the reaction mechanism. These predictions could be tested equally well with other isomers such as the K = 15 state in 184 Hf identified in storage-ring measurements [82,83].…”
Section: Isomer Beamsmentioning
confidence: 99%
“…One type of fission-like events was seen in interactions of heavy projectiles (e.g. 84 Kr), where the yield of (mass-symmetric) fusion-fission was found to be much lower than expected, and there was a large yield of fully damped events with some mass evolution towards symmetry [17]. This process was initially described as [17] "the deepest inelastic collisions", or alternatively "quasifission" [69].…”
Section: First Evidence For Quasifissionmentioning
confidence: 99%
“…This process was initially described as [17] "the deepest inelastic collisions", or alternatively "quasifission" [69]. Figure 1(a) shows the fragment mass vs. Total Kinetic Energy distribution, for binary reaction products in the 84 Kr + 186 W reaction forming Ds (Z=110). The spectrum was determined from the two fragment kinetic energies recorded using Si detectors at 40 degrees.…”
Section: First Evidence For Quasifissionmentioning
confidence: 99%
See 1 more Smart Citation